Otoritas Peradilan Islam dalam Lintasan Kolonial dan Pembentukan Hukum Nasional di Indonesia - Natsir, Abdul Husain; Asmira, Asmira; Mustafa, Zulhas’ari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the transformation of the authority of Islamic courts in Indonesia across the colonial and post-colonial periods and their contribution to the formation of national law. Employing a normative-juridical method with historical, statutory, and conceptual approaches drawn from library sources, the research traces how a once-autonomous Islamic judicial institution was reshaped by Dutch colonial legal politics, from the recognition implied by the receptio in complexu theory to the systematic reduction of competence under the receptie theory through Staatsblad 1882 No. 152 and Staatsblad 1937 No. 116 and 610. The findings show that the colonial intervention narrowed the jurisdiction of religious courts, particularly by removing inheritance disputes, yet did not extinguish their existence. After independence, the receptie exit and receptie a contrario theories provided the ideological basis for restoring Islamic judicial authority, institutionalized through the establishment of the Ministry of Religious Affairs, Law No. 14 of 1970, Law No. 1 of 1974, Law No. 7 of 1989, the Compilation of Islamic Law, and Law No. 3 of 2006. The study implies that the religious court has become an integral pillar of the national judicial system rather than a colonial remnant.